Professional Education between the 30's and 90's: a history of subordination to productive processes in the Brazilian context (Research, Society and Development, 2019)
Between the 1930s and 1990s, the years of Brazilian capitalist development, a series of changes in the organization of Brazilian society began. This article intends to analyze, from a historical perspective, the construction of the educational apparatus in the context of state industrialism, as well as the consolidation of the duality between propaedeutic and professional education, arising from this process. For the development of the present study, the qualitative approach was chosen, using the bibliographic research. For the bibliographic survey were selected different sources that could corroborate with a critical analysis of our object of study, namely: Professional Education in the Brazilian context. Thus, we present the History of Professional Education in Brazil, seeking to reflect on the relationship of the historical-economic context with the formation of the workforce. Finally, it is concluded that throughout Brazilian history, professional education reflects the power relations of a class-divided society, in which the exercise of intellectual and managerial functions is attributed to the elite and the exercise of operational and manual functions. to the working classes